2017
DOI: 10.1016/j.stemcr.2016.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Hippocalcin Promotes Neuronal Differentiation and Inhibits Astrocytic Differentiation in Neural Stem Cells

Abstract: SummaryHippocalcin (HPCA) is a calcium-binding protein that is restricted to nervous tissue and contributes to neuronal activity. Here we report that, in addition to inducing neurogenesis, HPCA inhibits astrocytic differentiation of neural stem cells. It promotes neurogenesis by regulating protein kinase Cα (PKCα) activation by translocating to the membrane and binding to phosphoinositide-dependent protein kinase 1 (PDK1), which induces PKCα phosphorylation. We also found that phospholipase D1 (PLD1) is implic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 61 publications
1
33
1
Order By: Relevance
“…These results strongly indicate that HPCA is required for the neuronal differentiation of SH-SY5Y cells. This is supported by a previous study showing that HPCA plays an important role in neuronal differentiation in various cell types, including H19-7 cells [28] and cortical neural stem cells [16]. …”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…These results strongly indicate that HPCA is required for the neuronal differentiation of SH-SY5Y cells. This is supported by a previous study showing that HPCA plays an important role in neuronal differentiation in various cell types, including H19-7 cells [28] and cortical neural stem cells [16]. …”
Section: Discussionsupporting
confidence: 83%
“…Previously, we reported that HPCA is critical for neuronal differentiation and neurite outgrowth in multiple cell types [16, 28]. To investigate whether HPCA was implicated in neuronal differentiation, either control siRNA or HPCA siRNA were transiently transfected into SH-SY5Y cells, which were then allowed to differentiate for 7 days.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations